Effect of nanosilica and nano zirconium oxide mixture modified by polydimethyl siloxane on the heat resistance of silicone paint - Nguyen Ba Ngoc (Journal of Military Science and Technology, 2025)
Silicone-based paints are known for their high-temperature resistance and durability in chemical environments. This paper presents research findings on a silicone paint formulation supplemented with a mixture of nano-silica and nano-zirconium oxide, which has been surface-modified with Polydimethylsiloxane (PDMS). The incorporated ratio was 0.45% modified nano-silica and 1.05% modified nano-zirconium oxide. Following thermal endurance evaluation (a thermal shock test conducted at 1,050 °C for 25 seconds), no micro-cracks were observed on the surface. This is attributed to the increased flexibility of the silicone coating at high temperatures and the more uniform dispersion of the modified nano-additive particles within the silicone resin matrix, thereby enhancing the thermal resistance of the paint film. The author also conducted a comparative heat resistance test using an acetylene torch, with the sample plate's exposure temperature reaching approximately 1,100 °C for a duration of 25 to 30 seconds. The performance of the modified nano-particle-containing silicone paint was compared against the BKV inorganic heat-resistant paint and alkyd paint on steel test panels from a CT-18 engine, yielding favorable results.